2008
DOI: 10.1103/physrevlett.100.217004
|View full text |Cite
|
Sign up to set email alerts
|

Time-Reversal Symmetry Breaking by a (d+id) Density-Wave State in Underdoped Cuprate Superconductors

Abstract: It was proposed that the id x 2 −y 2 density-wave state (DDW) may be responsible for the pseudogap behavior in the underdoped cuprates. Here we show that the admixture of a small dxy component to the DDW state breaks the symmetry between the counter-propagating orbital currents of the DDW state and, thus, violates the macroscopic time-reversal symmetry. This symmetry breaking results in a non-zero polar Kerr effect, which has recently been observed in the pseudogap phase. 74.25.Nf, 71.27.+a Introduction. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 20 publications
(21 reference statements)
4
65
0
2
Order By: Relevance
“…µSR 50 and polar Kerr effect 51 have established the onset of time-reversal-symmetry breaking (TRSB) at T * (p) in YBa 2 Cu 3 O 6+y , but the signals are extremely weak. It has been suggested that a variant of the DDW, the d xy + id x 2 −y 2 density wave, 52 would contain a subdominant but macroscopic TRSB component and be consistent with the small magnitude of the observed effects. Spin-polarized neutron scattering on YBa 2 Cu 3 O 6+y has detected weak signatures of a novel magnetic order that preserves translational symmetry, 53 and has a form consistent with the Θ II circulating current phase proposed by Varma,48 shown in schematic form in the inset of This paper is organized as follows.…”
mentioning
confidence: 84%
“…µSR 50 and polar Kerr effect 51 have established the onset of time-reversal-symmetry breaking (TRSB) at T * (p) in YBa 2 Cu 3 O 6+y , but the signals are extremely weak. It has been suggested that a variant of the DDW, the d xy + id x 2 −y 2 density wave, 52 would contain a subdominant but macroscopic TRSB component and be consistent with the small magnitude of the observed effects. Spin-polarized neutron scattering on YBa 2 Cu 3 O 6+y has detected weak signatures of a novel magnetic order that preserves translational symmetry, 53 and has a form consistent with the Θ II circulating current phase proposed by Varma,48 shown in schematic form in the inset of This paper is organized as follows.…”
mentioning
confidence: 84%
“…A model of this kind, involving formation of the d xy + id x 2 −y 2 density wave, was proposed in Ref. [78] to explain the Kerr effect in underdoped cuprates [2]. The anomalous Hall effect was studied for this model earlier in Ref.…”
Section: Appendix B: Chiral Superconductors Vs the Trsb Topological mentioning
confidence: 99%
“…For non-superconducting systems, the current operator can be expressed in terms of the derivatives ∂Ĥ/∂p of the HamiltonianĤ with respect to the electron quasimomenta p. For a topologically non-trivial band structure, the off-diagonal matrix elements of the current operator between different bands produce a non-zero Berry curvature, and the anomalous Hall conductivity can be expressed completely in terms of the Berry curvature [46,47,[77][78][79][80].…”
Section: Appendix B: Chiral Superconductors Vs the Trsb Topological mentioning
confidence: 99%
“…Here we show that the observations in high-T c can be understood in the framework of a chiral d-density wave state 30 in the presence of interlayer tunneling, which is invariant under TRS in the bulk, but can still have a non zero PKE because it is a property of the light reflected from the top surface which breaks TRS locally. Therefore PKE in this mechanism would be insensitive to the changing skin depth of the incom- ing light at the top surface, while PKE from a bulk order parameter based description would yield a stronger effect for a longer skin depth.…”
Section: Introductionmentioning
confidence: 99%